Unveiling Classroom Dynamics: Exploring Teaching and Learning Strategies through Interactional Features in ESP Classes - Akiko Rahmawati (Departement of Mathematics Education, 2024)
This study aimed to look into the teaching and learning strategies used by three participant classes, especially lecturers’ level of interaction with students which was observed through classroom observations. This also aimed to discover whether classroom interaction are effective in facilitating students learning. During the course of this study, the researcher observed three lessons of three different English for Specific Purpose classes, recorded them on video and transcribed, and analysed them using Walsh’s Self Evaluation Teacher Talk (SETT) framework. The researcher found out that classroom interaction fell into three categories: pre, side, and insertion sequences. Unfortunately, these sequences of interaction went not smooth in some sections. In addition, the interactional features in the classroom played an important role in ensuring that the interaction ran smoothly. Moreover, the data revealed 12 interactional features were found, they were scaffolding, direct repair, content feedback, extended wait time, referential question, display question, seeking clarification, confirmation check, extended learner’s turn, teacher echo, extended teacher’s turn, and form-focused feedback. As the result, the dynamic interaction in classroom could shape overall discourse which attempted to maintain the effective language use. Moreover teacher talk significances in fostering an optimal learning environment for students in ESP classes.